1,2,4-Thiadiazolidine derivative inhibits nuclear transcription factor-κB and its dependent genes activation but induces apoptosis - Manna, P.; Narang, K.K.; Manna, S.K. (My University, 2005)
The 1,2,4-thiadiazolidine derivatives have been shown to be involved in several biological responses such as anti-bacterial, antifungal, anti-tubercular and local anaesthetic activities. In our study, we have synthesized some new 5-substitutedarylimino-2-N-substitutedphenyl-3-oxo-1,2,4-thiadiazolidine and tested for anti-inflammatory and anti-tumor activities. The 5-(4- methoxyarylimino)-2-N-(3,4-dichlorophenyl)-3-Oxo-1,2,4-thiadiazolidine (P 3-25) showed anti-inflammatory activity as it inhibited different inflammatory inducers mediated nuclear transcription factor kappa B (NF-κB), a key transcription factor involved in all forms of inflammation, P3-25 inhibited TNF-induced NF-κB activation as detected by gel shift assay and dependent reporter gene expression. It inhibited IκBα degradation, IκB kinase activation and p65 nuclear translocation. P3-25 inhibited TNF-induced Cox2 expression. It inhibited NF-κB activation in human epithelial and T cells. Unlike other substitutary derivatives, P3-25 was a potent inducer of apoptosis as it induced cell death, caspase-dependent PARP cleavage, ROI generation and lipid peroxidation. Overall our results suggest that P3-25 derivative exerts anti-inflammatory and anti-tumor activities, which may have a role in designing such drugs.
Keywords: 1,2,4-thiadiazolidine; Apoptosis; Cell signaling; NF-κB; Tumor